Oxidative dissolution of chalcopyrite by Thiobacillus ferrooxidans - Bevilaqua-Mascarin, D. [UNESP]; Garcia, O. [UNESP]; Tuovinen, O. H. (Elsevier, 1999)
The oxidative dissolution of research-grade chalcopyrite was characterized in respirometric and growth experiments with Thiobacillus ferrooxidans. In respirometric experiments with chalcopyrite, the pH of mineral salts medium increased to values that inhibited the oxygen uptake activity of T. ferrooxidans. In glycine-H 2SO 4 buffered medium the pH remained stable and oxygen uptake was not inhibited. In cultures growing with chalcopyrite as the sole source of energy, pH changes were only minor during the incubation. The redox potential values increased to about 600 mV during the bacterial oxidation of chalcopyrite in the presence and absence of additional Fe 2+, while they remained at about 350 mV in abiotic control flasks. Iron in chalcopyrite was solubilized and oxidized to Fe 3+ by T. ferrooxidans. In the abiotic controls, by comparison, less iron was solubilized and it remained as Fe 2+. Jarosite was a major solid- phase product in T. ferrooxidans cultures. The solub'flization of copper from chalcopyrite in inoculated flasks was enhanced in the presence of additional Fe 2+.Accumulation of S 0, reflecting partial oxidation of the S-entity of chalcopyrite, was apparent from the x-ray diffraction analysis of solid residues from the inoculated flasks as well the abiotic controls. © 1997 Elsevier B.V. All rights reserved.